2012
DOI: 10.1051/ata/2013025
|View full text |Cite
|
Sign up to set email alerts
|

L’argon : utilisations, toxicité et stratégie analytique en toxicologie médicolégale

Abstract: Résumé -Bien qu'intrinsèquement non toxiques, les gaz nobles comme l'argon entraînent à fortes concentrations une déplétion d'oxygène pouvant mener jusqu'à l'asphyxie. Si l'argon se retrouve dans la circulation générale, celui-ci peut même être responsable d'embolies parfois fatales. Cependant, les propriétés d'inerties physicochimiques de ce gaz le rendent très utile dans de nombreuses applications actuelles. Ces applications étant en constante augmentation, il n'est pas rare d'observer proportionnellement de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Tissue samples were taken according to the particular standard procedure (rapid sampling during autopsy in HS vials of 10 or 20 mL, sealed with aluminium cap and cold storage). Gaseous samples were taken following the protocol of noble gases poisoning or intracadaveric gases [36][37][38].…”
Section: Collection Of Gas Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue samples were taken according to the particular standard procedure (rapid sampling during autopsy in HS vials of 10 or 20 mL, sealed with aluminium cap and cold storage). Gaseous samples were taken following the protocol of noble gases poisoning or intracadaveric gases [36][37][38].…”
Section: Collection Of Gas Samplesmentioning
confidence: 99%
“…Therefore, as a single lung biopsy cannot be representative of the whole organ, protocols using lung lobectomy (mono, bi, trilobular biopsies) have been developed to avoid false negative results due to sampling. These protocols have been well described [3,24,36,37,40,41] but some authors found them too sophisticated compared to rapid lung biopsy in HS [32]. However, this comment was formulated because the HS lungs biopsies were detected as He positive.…”
Section: Choice Of Samples: Lung Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas sampling under laser guidance is an efficient and precise tool to recover gas samples located into the body [19]. For suicide with noble gas, the samples of interest are gastric gas, tracheal gas and lungs samples [20]. These matrices can easily be sampled during conventional autopsy (with airtight gas syringe for gaseous samples) without the aid of forensic imaging.…”
Section: What Is the Analytical Strategy?mentioning
confidence: 99%